Aterros sobre solos compressíveis - cálculo automático da sua construção por etapas - Ferreira, Ronaldo da Silva (1977)
Present an automatic programme wich permits design and analysis of embankments built on compressible and low strengh soils. The programme deals with the step-by-step construction of the embankment and optimizes the rate of construction from the given data and required stability. The programme computes the rate of neutral pressure dissipation, the evolution of settlements and safety factor against rupture, and the size of the drains. The forecast of embankment behaviour is obtained by the execution of two main programmes, and mathematical calculations are performed by twenty-four sub-routines. At the outset there is a review of the pertinent literature in this field with special attention given to the study of the theories applied to the forecast of embankment behaviour. Considerations follow treating of the theoretical fundamentals inserted in the computer programmes presented under the form of activities executed in each of the principal programmes and each sub-routine. Later on, a user manual is presented for those who are interested in studying the behaviour of embankments on compressible soils. Finally, examples of programme appiication are studied with special reference to the experimental embankment of the IPR (Road Research Institute) to be constructed in the lowland areas in the state of Rio de Janeiro. We hope that this programme will be much useful for the engineers of the highway departments (DNER e DERs) and consulting firms dealing with such soil problems.